Prevalence of Sarcocystis neurona and Neospora spp. infection in horses from Brazil based on presence of serum antibodies to parasite surface antigen - Hoane, J. S.; Gennari, S. M.; Dubey, J. P.; Ribeiro, M. G.; Borges, A. S.; Yai, LEO; Aguiar, D. M.; Cavalcante, G. I.; Bonesi, G. L.; Howe, D. K. (Elsevier B.V., 2006)
Sera from 961 horses from Brazil were tested for antibodies against the major surface antigens SnSAG4 and NhSAG1 to determine the seroprevalence of Sarcocystis neurona and Neospora hughesi, respectively. Antibodies against SnSAG4 were detected in 669 (69.6%) of the horses, while antibodies against NhSAG1 were detected in only 24 (2.5%) of the horses. These serologic results suggest that there is a high concentration of S. neurona in the environment of Brazil, which results in marked exposure of horses to this parasite. Additionally, the data further confirm that infection with Neospora spp. is relatively uncommon in horses. (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Sarcocystis neurona; Neospora spp.; seroprevalence; horses; ELISA; Brazil